Pseudobranchellion margoi (nova Familia Hirudinearum) - Apáthy, Stephan | István (Orvos Természettudomanyi Értesitoe Kolozsvár, Budapest, 1890)
The new family is called the Chelyobdellidae and comes between the Ichthyobdellidae and Clepsinidae, in the group of the Rhynchobdellidae. The whole material obtained by author (several hundred specimens) was taken from one individual of Thalassochelys corticata in the Bay of Naples. [summary as in Zoological Record vol 28, 1881]
The pagination reported for the second version of the article translated into German was not found in the journal as online. In English the journal title would be "Bulletin of medical and natural sciences. II Natural Sciences major"